2003
DOI: 10.1063/1.1555273
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cap layer on implantation induced interdiffusion in InP/InGaAs quantum wells

Abstract: A comparison of spectroscopic and microscopic observations of ion-induced intermixing in InGaAs/InP quantum wells Appl. Phys. Lett. 72, 1599 (1998); 10.1063/1.121185Lateral selectivity of ion-induced quantum well intermixing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…The PL spectra of the H-implanted InP-capped samples annealed at 800 C for 30 s are shown in Figure 21 (Barik et al, 2006b). It has been reported that dynamic annealing in InGaAs is significant even at room temperature and is stronger than in InP (Carmody et al, 2003). This property has also been observed in other lowdose implanted samples annealed at temperatures in the entire temperature range used in this study.…”
Section: Inas/inp Qdssupporting
confidence: 75%
“…The PL spectra of the H-implanted InP-capped samples annealed at 800 C for 30 s are shown in Figure 21 (Barik et al, 2006b). It has been reported that dynamic annealing in InGaAs is significant even at room temperature and is stronger than in InP (Carmody et al, 2003). This property has also been observed in other lowdose implanted samples annealed at temperatures in the entire temperature range used in this study.…”
Section: Inas/inp Qdssupporting
confidence: 75%
“…Note that the density and diffusion range of these defects depend on the ridge geometry; both quantities are increased for narrow and high ridges. Phosphorus has a large self-diffusion coefficient, 13 which makes phosphorus interstitials optimal candidates to be dominant defects inside the ridge. The source of these interstitials is not well understood at present, since they have to be generated at the InP-dielectric capping layer interface; one could tentatively argue that the excess phosphorus accumulated at the surface 18 could constitute the source of in-diffusing P.…”
Section: Stress Modelmentioning
confidence: 99%
“…On the other hand, one has to consider the nature of the mask, as the use of SiO x or SiN x has been demonstrated to impact on the intermixing phenomena, because of the difference between the defect types generated. 13 Samples etched using different mask dimensions and with different etching times, resulting in ridge waveguides of different dimensions (width and height), were studied. Top-view CL images of different waveguides are shown in Fig.…”
Section: Intensity Distributionmentioning
confidence: 99%
“…Implantations were performed at 7°off the ͑001͒ direction to minimize channeling effects. The substrate temperature was maintained at 200°C to prevent surface amorphization 6 and the implantation fluence ⌽ ranged from 5 ϫ 10 11 to 10 14 cm −2 . Based on SRIM 2000 simulations, 24 the energy of P ions was set to 30 keV to confine implantation damage to the first 120 nm below the top surface ͓see Fig.…”
Section: Methodsmentioning
confidence: 99%